Establishing new factory with technology certification roadmap - Mohiuddin, A. K. M.; Quick, Wee Hock (2004)
Today market volatility and stiff competitiveness call for greater agility and mobility of setting and shifting manufacturing plants worldwide. Notwithstanding the complexities involved, the challenge is not constraint to just transfer of machines and technology but including plant-wide proven standard performance and competencies. Essentially, the expectation is to ramp-up manufacturing capacity within a shortest time possible and concurrently developing fundamental competencies, equivalent to that of any established sites. The purpose is to demonstrate how critical to success factors are developed into an interactive dynamic system and interwoven into the integral operational system. In every sense, this model has, from time to time - proven to be a forerunner in streamlining business process, reducing product time to market and developing sustainable competitive advantage.